A Case of Complete Heart Block With Diagnostic Challenge and Therapeutic Dilemma. (12th July 2018) - Yang, Ying Chi; Pata, Rama Kanth; Aung, Thein Tun
Permanent pacemaker implantation is a class I indication for all symptomatic patients with complete heart block either congenital or acquired. However, certain portions of patients with congenital complete heart block are asymptomatic. Those patients are often very young, and implanting a permanent pacemaker is not always an easy decision. A therapeutic dilemma arises when a select patient population does not meet certain criteria to gain the maximum benefits out of prophylactic pacemaker therapy. Most asymptomatic patients with congenital complete heart block will eventually become symptomatic and require pacemakers at some point in their life but the definitive answer for the ideal time to initiate pacemaker therapy in such population has not been established. We present a case of asymptomatic congenital complete heart block with junctional escape rhythm, which is capable of incrementing the heart rate with physical activity to result in a challenge in diagnosis as well as the treatment strategy.